SYNTHESIS OF COUMARIN HETEROCYCLIC DERIVATIVES WITH IN-VITRO ANTITUBERCULER ACTIVITY - Godge, Rahul; Kunkulol, Rahul (Journal of Drug Delivery and Therapeutics, 2018)
In last few decades, though significant progress has been made in the treatment and control strategies of tubercular infections by introducing new diagnostic and monitoring tools and combination therapy, it still continues to be severe problem. The need of study was only because of there are many drugs in market to treat infection but most of the drugs are showing resistance because of the same it is difficult to treat the infection. In this study we chosen coumarin nucleus for study. Thus with the aim of developing novel molecule with improved potency for treating Mycobacterium tuberculosis H37Rv strain infections and with decreased probability of developing drug resistance. The synthesis of coumarin derivatives, starting from salicyaldehyde and ethyl acetoacetate, by conventional organic reaction and results of investigations of their anti-mycobacterial activity. MICs of the synthesized compounds are compared with existing drugs Cytotoxicity. Many compounds have shown promising activity while some were inactive. It was found that Compound A1, A2, B1, B2, C1, C2 have shown promising antitubercular activity against std. Streptomycin Keywords: Coumarin derivative, well diffusion method, antitubercular activity.